2021
DOI: 10.1111/1471-0528.16758
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and clearance of high‐risk human papillomavirus and cervical dysplasia at 1 year in women living with human immunodeficiency virus: a prospective cohort study

Abstract: Objective Evaluate 1-year outcomes of cervical cancer screening and treatment using primary high-risk human papillomavirus (HPV) testing in women living with human immunodeficiency virus (HIV).Design Prospective cohort study.Setting HIV treatment centre in Botswana.Population Women living with HIV.Methods Participants underwent cervical cancer screening with high-risk HPV testing and triage evaluation at baseline and 1-year follow up. Excisional treatment was offered as indicated. Histopathology was the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Among 237 WLWH who returned for follow-up, the prevalence of CIN2+ was 9%, similar to the baseline prevalence of 8%. Incident CIN2+ among WLWH who were HR-HPV-negative at baseline was 5.3%, 10 times that in Kelly's study [17 ▪▪ ,30 ▪▪ ]. Although the numbers were small, there was a 40% (8/20) progression from no cervical disease to CIN2+ among WLWH who were HR-HPV positive at baseline [30 ▪▪ ].…”
Section: Human Papillomavirus-based Preventionmentioning
confidence: 68%
See 1 more Smart Citation
“…Among 237 WLWH who returned for follow-up, the prevalence of CIN2+ was 9%, similar to the baseline prevalence of 8%. Incident CIN2+ among WLWH who were HR-HPV-negative at baseline was 5.3%, 10 times that in Kelly's study [17 ▪▪ ,30 ▪▪ ]. Although the numbers were small, there was a 40% (8/20) progression from no cervical disease to CIN2+ among WLWH who were HR-HPV positive at baseline [30 ▪▪ ].…”
Section: Human Papillomavirus-based Preventionmentioning
confidence: 68%
“…Of those HR-HPV positive without CIN2+ at baseline, incident CIN2+ was 5.8%, whereas only 0.5% baseline HR-HPV-negative women developed incident CIN2+ at 16 months [17 ▪▪ ]. Luckett et al [30 ▪▪ ] reported higher rates of incident CIN2+ at 12–16 months among women who were baseline HR-HPV-negative [30 ▪▪ ]. Among 237 WLWH who returned for follow-up, the prevalence of CIN2+ was 9%, similar to the baseline prevalence of 8%.…”
Section: Human Papillomavirus-based Preventionmentioning
confidence: 99%
“…20 Rates of concordant results between AmpFire and Roche linear array HPV on anal swabs was similarly high (90%). 17 In a population of women living with HIV, vaginal self-swabs were found to have 89% positive agreement between AmpFire and Xpert, with AmpFire being slightly more likely to diagnose HPV than Xpert. 28 Beyond agreement in HPV results, our ndings demonstrate the accuracy of AmpFire in identifying women with CIN2+, data which few other studies have con rmed.…”
Section: Discussionmentioning
confidence: 98%
“…Vaginal self-swabs had > 95% agreement between AmpFire, both Roche Cobas® 4800 HPV assay, and SeqHPV assay [ 20 ]. Rates of concordant results between AmpFire and Roche linear array HPV on anal swabs was similarly high (90%) [ 17 ]. In a population of women living with HIV, vaginal self-swabs were found to have 89% positive agreement between AmpFire and Xpert, with AmpFire being slightly more likely to diagnose HPV than Xpert [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Botswana has excellent laboratory infrastructure to perform laboratory-based HPV testing, implementation of HPV testing at the national level is hindered by the cost of HPV testing [ 16 ]. In our research setting, high-risk HPV genotyping has been performed with the Xpert® HPV Assay and the Abbott RealTime® HPV assay, which both test for the same 14 high-risk HPV genotypes [ 17 ]. While the performance of these tests in a research setting was satisfactory, their cost prohibits national implementation of primary HPV screening, despite demonstration that HPV-based screening is the most effective method to screen our population.…”
Section: Introductionmentioning
confidence: 99%